Membangun Kesadaran Masyarakat Tentang Pentingnya Pendidikan Melalui Kuliah Kerja Nyata ( KKN ) Di Desa Maju Jaya Kecamatan Pelepat Ilir Kabupaten Bungo Jambi - Enramika, Tomi; Riadi, M. Irfan; Deni Priyanto; Anjar Muanifah; Suhartati; Ridwan (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Through Real Work Lecture (KKN) activities, we are required to practice science and also benefit the village. We are expected to be motivators and facilitators of development efforts, especially in rural areas. The community can share existing problems and find solutions by participating in KKN, establishing cooperation in the development process in the local area. Based on the results of a survey conducted by researchers in the field of education in Maju Jaya Village, it was found that some people still do not consider education too important, and there are still children who drop out of school. One of the objectives of this KKN activity is to change the mindset of the community about education and provide motivation for the people of Maju Jaya Village to continue their education at every level. This community service activity in the form of KKN lasts for one month, and the method carried out to obtain this data is to use observation and interviews directly with the community. The implementation of this KKN activity is carried out in the form of socialization and activities by involving the community directly. Some of the results achieved from this KKN activity include helping the community increase awareness of the importance of Education and providing motivation and solutions to Education problems.